2022
DOI: 10.3171/case21135
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality–assisted microsurgical resection of brain arteriovenous malformations: illustrative case

Abstract: BACKGROUND Arteriovenous malformations (AVMs) of the brain are vessel conglomerates of feeding arteries and draining veins that carry a risk of spontaneous and intraoperative rupture. Augmented reality (AR)-assisted neuronavigation permits continuous, real-time, updated visualization of navigation information through a heads-up display, thereby potentially improving the safety of surgical resection of AVMs. OBSERVATIONS The authors report a case of a 37-year-old female presenting with a 2-year history of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In our case, the surgical set up resembled the microsurgical resections performed by Scherschinski et al [ 13 ] and Cabrilo et al [ 14 ] who had integrated preoperative radiological data with the stereotactic navigation process. The virtual anatomical hologram projecting onto the cortical surface helps the operator identify complex angioarchitecture under the microscope.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our case, the surgical set up resembled the microsurgical resections performed by Scherschinski et al [ 13 ] and Cabrilo et al [ 14 ] who had integrated preoperative radiological data with the stereotactic navigation process. The virtual anatomical hologram projecting onto the cortical surface helps the operator identify complex angioarchitecture under the microscope.…”
Section: Discussionmentioning
confidence: 93%
“…For example, neurosurgeons may get distracted due to the need to look away from the surgical field seen under the microscope in order to focus attention on an external monitor. To address any limitations these systems may cause, Augmented Reality (AR) surgical technology was designed to reduce distracting factors, while also providing surgeons with real-time feedback regarding vascular morphology and location [ 10 , 11 , 12 , 13 ]. In this case report, we present a patient who has been diagnosed with intracranial AVM and subsequently received AR-assisted microsurgery for lesion resection.…”
Section: Introductionmentioning
confidence: 99%
“…It has been consistently shown that VR-assisted teaching helps enhance the quality of instant instruction in the clinical medical area. For example, in the field of surgical medicine, VR is currently used for a variety of purposes, including the exploration of potential new surgical plans [ 48 ], the design of surgical plans prior to surgery [ 49 ], the improvement of clinicians' operational skills and the reduction of the surgical learning curve [ 50 ], the direction of patients during postoperative repair [ 51 , 52 ], etc. Despite the positive outcomes in the aforementioned areas, creating certain unique therapeutic situations demands a significant financial commitment owing to the high cost of VR learning and the complicated and variable clinical scenarios [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…transparent displays that present data without requiring users to look away from their viewpoint), head-mounted display (i.e. devices which are worn on the head or as part of a helmet), monitor- and tablet-based visualisation, and image insertion into the surgical field, have been investigated [ 3 , 13 , 14 , 19 , 30 , 39 , 47 , 49 , 62 , 73 , 81 , 93 ].…”
Section: Discussionmentioning
confidence: 99%